National trends in the use of oral chemotherapy over 13 years - Moreira, A.; Bernardo, C.; Ramos, C.; Aguiar, P.; Alves da Costa, F. (Frontiers in Pharmacology, 2022)
Background: Systemic cancer therapy has traditionally been administered using intravenous route, implying patients’ frequent visits to hospitals to access to their therapy. If we consider the actual pipeline in oncology, oral chemotherapy will be the main component of cancer treatment in the next years. This shift in administration route requires different care models in order to guarantee treatment efficacy and safety. Objective: To analyze time trends in oral chemotherapy consumption in Portugal. Method: Oral chemotherapy consumption over a thirteen-year period (2008-2020) was analyzed, considering dispensed units by administration route with respective costs, resorting to the drug regulatory agency (INFARMED I.P.) database. Oral consumption patterns were further explored using common daily doses (CDD) for three conditions Chronic Myeloid Leukemia (CML), Non-small cell lung cancer (NSCLC) and Breast Cancer (BC) to adjust for the effect of varying doses. Data were analyzed descriptively resorting to Microsoft Office Excel 2010. Results: Overall chemotherapy consumption increased +Δ54.7%, with the highest contribution in units observed in oral forms (+Δ58.8%). Total expenditure increased +Δ96.5%, and despite the increase in oral forms (+Δ221.6%), intravenous forms continued to be the major cost driver, with an important contribution from immunotherapy. Much of the increase was led by the approval of 40 new IV and 48 new oral cancer medications with higher costs introduced in the market. Using CDD as an alternative metric to units had varying impact by indication. Increases observed seemed to focus on specific cancer sites with varying effect; in CML, there was a 2.39-fold increase, compared to 4.41 for NSCLC and 1.86 for BC. However, for BC, two distinct sub-patterns were observed for hormone therapy (increasing 1.83) and for the novel tyrosine kinase inhibitors (increasing 40.8). Conclusion: The growing use of oral chemotherapy is obvious and calls for investments in supporting patients in managing medication adherence and adverse events. Shifts in healthcare system organization are complex and need to be prioritized. Our data suggests priority could be attributed to cancer sites driving innovation, namely advanced breast cancer.